Komparasi Tingkat Kesehatan Bank Syariah dan Bank Konvensional dengan Pendekatan Risiko - Fahmi Alif Firmansyah; Esy Nur Aisyah (SAFE-Network, 2023)
This research aims to find out how the health level of Sharia Banks and Conventional Banks compares using the Risk-Based Bank Rating (RBBR) method. This research is quantitative research with comparative methods. This research data uses secondary data taken from the Bank Indonesia website. This research data analysis uses comparative quantitative statistics. The total sample is 10 banks consisting of 5 sharia banks and 5 conventional banks. The research results show that there is a significant (real) difference between the average value of credit risk in Islamic banks and conventional banks. There is no significant (real) difference between the average value of liquidity risk in Islamic banks and conventional banks. There is a significant (real) difference between the average Return on Asset (ROA) value for Islamic banks and conventional banks. There is no significant (real) difference between the average Net Interest Margin (NIM) value of Islamic banks and conventional banks. There is a significant (real) difference between the average Capital Adequacy Ratio (CAR) value for Islamic banks and conventional banks.